From «Arte Povera» to the Poor Pedagogy: the art of transforming the ephimeral into intensity - Esteruelas Teixidó, Albert; Laudo Castillo, Xavier (Historia y Memoria de la Educación, 2016)
The present article seeks to recover some pedagogical ideas forgotten and abandoned by current mainstream pedagogy. Namely, it refers to ideas taken from art and history, «useless» models that deviate from the «useful» positivistic, materialistic and commercial ideas that are shaping the future of pedagogy. First, we briefly describe the movement founded by Germano Celant in 1967 known as «arte povera», noting that there are innumerable thought constructions related to his work that are relevant for pedagogy. «Poor pedagogy» emerges from the comparison between «arte povera» and pedagogy, a concept that recycles ideas that have fallen into oblivion despite their enormous interest. Secondly, we characterize the poor pedagogy by comparing it with productions and conceptions of arte povera, the result being the enumeration and development of a set of features that, while not exhausting the possibilities of the povera phenomenon, amount to what we call «poverism».